2022
DOI: 10.1109/tcbb.2020.3030312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Existing Methods for High-Order Epistasis Detection

Abstract: Finding epistatic interactions among loci when expressing a phenotype is a widely employed strategy to understand the genetic architecture of complex traits in GWAS. The abundance of methods dedicated to the same purpose, however, makes it increasingly difficult for scientists to decide which method is more suitable for their studies. This work compares the different epistasis detection methods published during the last decade in terms of runtime, detection power and type I error rate, with a special emphasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…MI quantifies the degree of association between the genotype distribution of cases and controls and the phenotype distribution obtained from the previously calculated contingency table. MI has shown a very good detection power in our previous comprehensive study [12], and the presence of low frequencies in the data, which become more prevalent as we move towards larger combination sizes, do not seem to be a problem.…”
Section: Mutual Information Calculationmentioning
confidence: 61%
See 2 more Smart Citations
“…MI quantifies the degree of association between the genotype distribution of cases and controls and the phenotype distribution obtained from the previously calculated contingency table. MI has shown a very good detection power in our previous comprehensive study [12], and the presence of low frequencies in the data, which become more prevalent as we move towards larger combination sizes, do not seem to be a problem.…”
Section: Mutual Information Calculationmentioning
confidence: 61%
“…For this reason, a multitude of methods have been proposed in order to solve this problem, many of which refrain from exploring every combination and, instead, implement non-exhaustive alternatives ranging from greedy algorithms to machine learning techniques (see, for instance, [6,8,9,10,11]). In a previous study [12], we compared the performance of all epistasis detection methods published during the last decade that offer an implementation available to the scientific community, when locating epistatic interactions of different orders. The study concludes that, despite the rich variety of methods, only the exhaustive approaches (those which explore every combination of loci up to a certain combination size) can reliably identify interactions with no marginal effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiuncho, as MPI3SNP [4], uses a Mutual Information (MI) based association test. As shown in [2], MI obtains a very good detection power.…”
Section: Introductionmentioning
confidence: 83%
“…Consequently, they allow for larger GWAS analysis at the cost of the possibility of not finding the target variant combination. Prior to this work, the performance of exhaustive and non-exhaustive methods has been studied thoroughly in [2]. The paper concluded that exhaustive methods are the only ones capable of identifying epistasis interactions in the absence of marginal effects.…”
Section: Introductionmentioning
confidence: 99%